2019
DOI: 10.1002/ejoc.201901239
|View full text |Cite
|
Sign up to set email alerts
|

Practical Cleavage of Acetals by Using an Odorless Thiol Immobilized on Silica

Abstract: A practical, efficient and general method was developed for the deprotection of a variety of aromatic and aliphatic acetals to their corresponding catechol or diol derivatives using thiol immobilized on silica gel. This is an application for the well-known commercial solid-supported thiol (SiliaMetS® Thiol). The procedure is mild and amenable to scale-up. It does not [a] Scheme 2. Cleavage of unsubstituted oxazolidines using Si-Thiol to give 1,2amino alcohols derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[42] We finally demonstrated that the scope of our B 2 -PAHs goes beyond the synthesis of aryl halides and reaches out to vicinally dihydroxylated PAHs: upon treatment with m-chloroperbenzoic acid (m-CPBA), 1 BOH is readily transformed to 2,3-dihydroxynaphthalene 1 OH (Scheme 2b). [43] Compounds of this kind have been used by Bunz and co-workers for the preparation of N-heteroacenes. [15] Based on a boron/iodine exchange protocol, we devise a universal method for the vicinal diiodination of PAHs.…”
mentioning
confidence: 99%
“…[42] We finally demonstrated that the scope of our B 2 -PAHs goes beyond the synthesis of aryl halides and reaches out to vicinally dihydroxylated PAHs: upon treatment with m-chloroperbenzoic acid (m-CPBA), 1 BOH is readily transformed to 2,3-dihydroxynaphthalene 1 OH (Scheme 2b). [43] Compounds of this kind have been used by Bunz and co-workers for the preparation of N-heteroacenes. [15] Based on a boron/iodine exchange protocol, we devise a universal method for the vicinal diiodination of PAHs.…”
mentioning
confidence: 99%
“…With a robust and scalable route to allyl benzene 9 , we shifted our focus toward the cyclization chemistry. Considering the multiple roles that BF 3 ·Et 2 O could play, it was anticipated that simultaneous deprotection, rearrangement, and cyclization of alkenyl benzene 9 to afford (+)-strongylin A might be possible under some certain conditions in the presence of BF 3 ·Et 2 O. However, treatment of 9 with BF 3 ·Et 2 O resulted in the deprotection of acetonide and subsequent cyclization to give benzopyran 10 , while the expected rearrangement process to facilitate the synthesis of (+)-strongylin A did not occur (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…So, a hydroxyl group was introduced to enones 29a and 29c by Davis’ oxidation to produce corresponding α-hydroxyketone, which was aromatized under CuBr 2 to obtain o -diphenol 31a in 75% yield . Next, acid 32a was prepared through the protection of two phenolic hydroxyl groups in 31a , followed by hydrolysis. Acid 32a was first treated with oxalyl chloride to furnish the acyl chloride, which was then reacted with an ethereal diazomethane to produce the key diazo ketone 33a in 69% yield .…”
mentioning
confidence: 99%